2003
DOI: 10.1046/j.1472-8206.2003.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Warming and response to contractile agents in calf cardiac vein: role of the nitric oxide

Abstract: The effects of warming on the response to various contractile agents of calf cardiac vein were studied using 2.5-mm long cylindrical segments. Concentration-response curves for carbachol (10(-9)-3 x 10(-4) m), 5-hydroxytryptamine (5-HT; 10(-8)-3 x 10(-3)), potassium chloride (KCl; 10(-4)-5 x 10(-2) m) and calcium chloride (CaCl2; 10(-4)-10(-2)) were isometrically recorded at 37 and 41 degrees C (warming). During warming the sensitivity, but not the maximal response, of carbachol 5-HT, KCl, and CaCl2 was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
(53 reference statements)
2
4
0
Order By: Relevance
“…In the present study, we also investigated the role of nitric oxide in cooling-and warming-induced responses. In previous studies, we observed similar findings in different tissues such as rabbit aorta [14], calf coronary artery and cardiac vein [15,16]. This suggested that during cooling or warming the response to the vasoconstrictors is not modulated by nitric oxide.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the present study, we also investigated the role of nitric oxide in cooling-and warming-induced responses. In previous studies, we observed similar findings in different tissues such as rabbit aorta [14], calf coronary artery and cardiac vein [15,16]. This suggested that during cooling or warming the response to the vasoconstrictors is not modulated by nitric oxide.…”
Section: Discussionsupporting
confidence: 83%
“…In addition to agonist-mediated constriction, limited evidence suggests that vascular smooth muscle responsiveness to nitric oxide and related factors can be influenced by temperature [11][12][13]. Recently, we studied the effects of temperature on the contractile response of smooth muscle in various species and vessels, and observed that the contractile responses were temperature-dependent but endothelium seems to have no role in the temperature-induced responses [14][15][16].Thus, despite current research to determine the effects of temperature on vascular reactivity of different animals species, studies with human tissues remain incompleteThe effects of cooling (to 28°C) and warming (to 41°C) on the vasoconstrictions induced by 5-hydroxytryptamine (5-HT) and acetylcholine (ACh) and the role of nitric oxide in these effects were analyzed in human umbilical artery and vein. 5-HT (10 )9 -10 )4 M) and ACh (10 )9 -10 )4 M) induced concentration-dependent contractions at 37, 28 and 41°C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To my knowledge, this is the fi rst study to show the effects of PDE inhibition of calf cardiac vein contracted with carbachol. In different studies it is reported that cooling (to 28 °C) induced subsensitivity (21) and warming (to 41 °C) induced supersensitivity (22,23) to carbachol in calf cardiac vein. In these studies, it has also been observed that endothelial nitric oxide does not play a role in the decreased sensitivity of noncutaneous vessels to contractile agents during cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary venous system (cardiac veins) collects one-third blood of the coronary circulation and is considered to be an important site for the blood-tissue exchange of water and nutrients, as well as a possible determinant of ventricular distensibility. The temperature utilized in this study; 28 °C, for cooling was considered to be "moderate cooling" and 41 °C, "moderate warming" temperature accordingly to previous studies (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%